Harnessing Artificial Intelligence for Sustainable Agriculture: A Comprehensive Scientometric Review - Kaur, Hardeep; Priya, Bhanu; Singh, Kuldeep (Recent Advances in Food Nutrition & Agriculture, 2025)
Agriculture empowers the economies of most developing countries as it contributes to the GDP and provides employment to half of the population. To augment the functionalities of agriculture, Artificial Intelligence (AI) has emerged as a significant solution. Consequently, substantial research endeavours have been carried out in this direction lately. However, a comprehensive study and scientometric analysis highlighting the potential of AI in agriculture has not been reported in the literature. Therefore, the presented scientometric study depicts the evolution of the pattern of research related to Artificial Intelligence technologies in agricultural practices based on the bibliographic data obtained from Scopus from 2015 to 2024. The data was analyzed and visualized using VOSviewer and Bibliometrix software by examining the publication growth trends, keyword co-occurrence networks, co-authorship networks, co-citation networks, institutional coupling networks, and journal coupling networks. The presented research concluded that India excels in the field, contributing 874 research documents, a substantial portion of the global total of 1,938. As per the link strength, China has secured the top position with 56 links and a total link strength of 1,080, while India follows closely in second place with 56 links and a total link strength of 871. The leading institution funding researchers with the highest number of publications is ICAR, while Science of the Total Environment stands out as the most relevant journal for disseminating their findings. The research topics explored involve using AI for disease detection, addressing nutrient deficiencies, analyzing soil content, and optimizing irrigation schedules. A notable emerging research topic highlights the effectiveness of AI in terms of increasing yield in agriculture. The future of AI in agriculture includes supply chain optimization, task automation, and climate adaptability, boosting food security and sustainability.
Keywords: Agriculture